2016
DOI: 10.14245/kjs.2016.13.4.177
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Range of Motion at Anterior Compression of the Cervical Cord after Laminoplasty in Patients with Cervical Spondylotic Myelopathy

Abstract: ObjectiveDegenerative diseases of the spine, such as cervical spondylotic myelopathy (CSM), are increasing among the old age population, and surgical treatment of CSM is becoming more and more common. The aim of this study was to investigate how functional recovery can be influenced by anterior compression of the spinal cord (ACS) after laminoplasty for treatment of patients with CSM.MethodsWe retrospectively analyzed 32 patients admitted to Ewha Womans Mok-Dong Hospital with CSM who underwent open-door lamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 95%
See 4 more Smart Citations
“…However, they did not describe the preservation of the muscle attachment at the C2 level in the technique. Conversely, Cho [37] and Sakaura et al [40] preserved the C2 muscle attachment in their technique, and this resulted in lesser loss of cervical lordosis than that reported by Uehara et al [34]. Interestingly, Su et al [36] reported lesser loss of cervical lordosis after performing C3-C6 laminoplasty without preserving the C2 muscle attachment.…”
Section: Radiological Outcomementioning
confidence: 95%
“…Technique with preservation of C2 and C7 muscle attachment may reduce the risk of cervical ROM loss. Cho [37] demonstrated that they only preserved C2 muscle attachment; their study showed the lowest loss of cervical ROM. However, in their study, above 70% of their technique did not involve C7 in the extent of laminoplasty.…”
Section: Radiological Outcomementioning
confidence: 97%
See 3 more Smart Citations